Enhancing Awareness of Gastritis Risk Due to Excessive Coffee Consumption Among Generation Z at Grandmed Hospital Lubuk Pakam - Purba, Anita Sri Gandaria; Reza, Muhammad; Suharnida, Yuni; Waruwu, Ria Aprilia; Syahfaradila, Syahfaradila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
Coffee is one of the most favored beverages globally, including in Indonesia. High work pressure and busy daily activities have encouraged increased coffee consumption, particularly among Generation Z, to maintain alertness and performance. However, excessive coffee intake may elevate the risk of gastritis. Gastritis is an inflammation of the gastric mucosa, which can be triggered by various factors, including high caffeine consumption. This Community Service (PkM) program aimed to raise awareness among Generation Z regarding the potential risk of gastritis due to uncontrolled coffee intake. The activity was conducted using a participatory educational approach, enabling participants to engage actively in the learning process. Educational content was delivered through lectures, discussions, and the distribution of informative leaflets to enhance participants’ knowledge. The activity began with a pre-test and concluded with a post-test to assess knowledge improvement. The participants consisted of Generation Z adolescents aged 17 to 25, who were visitors or interns at Grandmed Hospital, Lubuk Pakam. The results revealed that 17 participants (85%) regularly consumed at least one cup of coffee daily, and 15 participants (75%) frequently experienced gastric discomfort following coffee consumption. After the educational session, there was an average knowledge increase of 28.5 points, and 19 participants (95%) showed improved scores and expressed satisfaction with the PkM program. This community service activity has proven effective in increasing public awareness, promoting proper coffee consumption behavior, and potentially reducing the risk of gastritis.